Highly Efficient Expression of Interleukin-2 under the Control of Rabbit β-Globin Intron II Gene Enhances Protective Immune Responses of Porcine Reproductive and Respiratory Syndrome (PRRS) DNA Vaccine in Pigs - Du, Yijun (Public Library of Science, 2014)
Highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) had caused catastrophic losses in swine industry in China. The current inactivated vaccine provided only limited protection, and the attenuated live vaccine could protect piglets against the HP-PRRSV but there was a possibility that the attenuated virus returned to high virulence. In this study, the eukaryotic expression vector pVAX1(©) was modified under the control of rabbit β-globin intron II gene and the modified vector pMVAX1(©) was constructed. Porcine interleukin-2 (IL-2) and GP3-GP5 fusion protein of HP-PRRSV strain SD-JN were highly expressed by pMVAX1(©). Mice inoculated with pMVAX1(©)-GP35 developed significantly higher PRRSV-specific antibody responses and T cell proliferation than those vaccinated with pVAX1(©)-GP35. pMVAX1(©)-GP35 was selected as PRRS DNA vaccine candidate and co-administrated with pVAX1(©)-IL-2 or pMVAX1(©)-IL-2 in pigs. pMVAX1(©)-IL-2+pMVAX1(©)-GP35 could provide enhanced PRRSV-specific antibody responses, T cell proliferation, Th1-type and Th2-type cytokine responses and CTL responses than pMVAX1(©)-GP35 and pVAX1(©)-IL-2+pMVAX1(©)-GP35. Following homologous challenge with HP-PRRSV strain SD-JN, similar with attenuated PRRS vaccine group, pigs inoculated with pMVAX1(©)-IL-2+pMVAX1(©)-GP35 showed no clinical signs, almost no lung lesions and no viremia, as compared to those in pMVAX1(©)-GP35 and pVAX1(©)-IL-2+pMVAX1(©)-GP35 groups. It indicated that pMVAX1(©)-IL-2 effectively increases humoral and cell mediated immune responses of pMVAX1(©)-GP35. Co-administration of pMVAX1(©)-IL-2 and pMVAX1(©)-GP35 might be attractive candidate vaccines for preventing HP-PRRSV infections.